2014
DOI: 10.1002/marc.201400559
|View full text |Cite
|
Sign up to set email alerts
|

Super Hydrogen and Helium Barrier with Polyelectolyte Nanobrick Wall Thin Film

Abstract: In an effort to impart light gas (i.e., H2 and He) barrier to polymer substrates, thin films of polyethylenimine (PEI), poly(acrylic acid) (PAA), and montmorrilonite (MMT) clay are deposited via layer-by-layer (LbL) assembly. A five "quadlayer" (122 nm) coating deposited on 51 μm polystyrene is shown to lower both hydrogen and helium permeability three orders of magnitude against bare polystyrene, demonstrating better performance than thick-laminated ethylene vinyl-alcohol (EVOH) copolymer film and even metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…These results demonstrate the lowest oxygen permeability ever reported for any thin film and the ability of LbL assembly to impart super gas barrier behavior to polymer films with only 16 total layers (very few when compared to most LbL assemblies) and a thickness of just 51 nm. Tzeng et al showed that these films also exhibit barrier to hydrogen and helium gas . Similar quadlayer films were also shown to exhibit excellent mechanical behavior .…”
Section: Layer‐by‐layer Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate the lowest oxygen permeability ever reported for any thin film and the ability of LbL assembly to impart super gas barrier behavior to polymer films with only 16 total layers (very few when compared to most LbL assemblies) and a thickness of just 51 nm. Tzeng et al showed that these films also exhibit barrier to hydrogen and helium gas . Similar quadlayer films were also shown to exhibit excellent mechanical behavior .…”
Section: Layer‐by‐layer Assemblymentioning
confidence: 99%
“…Tzeng et al showed that these fi lms also exhibit barrier to hydrogen and helium gas. [ 132 ] Similar quadlayer fi lms were also shown to exhibit excellent mechanical behavior. [ 112 ] Quadlayers of poly(vinyl amine)(PVAm)/PAA/PVAm/ MMT, hydrophobically modifying PEI with pyrene groups (PEI-Py/PAA/PEI-Py/MMT), and all naturally derived CH/λ-Carrageenan(CR)/CH/MMT have also been shown to reduce the oxygen transmission rate of the substrate by at least two orders of magnitude while remaining less than 150 nm thick.…”
Section: Quadlayer and Trilayer Assembliesmentioning
confidence: 99%
“…PS substrate was used for background subtraction to correct each spectrum. Gas permeability coefficients of CO 2 and N 2 were measured using a previously described apparatus and procedure . Measurements were carried out at 20, 35, and 50 °C using UHP grade gases.…”
Section: Methodsmentioning
confidence: 99%
“…Best-performing polymeric materials are polyvinyl difluoride, polyester, polyamide, and ethylene vinyl alcohol copolymers (EVOH). For the latter, a 20 μm film, for instance, shows a He transmission rate as high as 160 cm 3 m –2 day –1 atm –1 . , …”
mentioning
confidence: 98%
“…The permeability of polymer films can be reduced in a nonselective manner by elongating the diffusion path of permeates via the incorporation of platy, crystalline, and therefore impermeable inorganic fillers. , This tortuous path approach has long been established by Cussler et al . (Figure c) and is highly nonlinear with respect to both the filler content and the aspect ratio of the platy filler (eq ).…”
mentioning
confidence: 99%